Producing Active Secondary Metabolite Against Pathogenic Vibrio spp. by Actinobacteria-Sodium Alginate Co-Culture - Nuril Azhar; Ervia Yudiati; Subagiyo Subagiyo; Rabia Alghazeer (Marine Science Department Diponegoro University, 2021)
Vibrio vulnificus, Vibrio parahaemolyticus and Vibrio harveyi have been found in aquatic environments and suspected as the primary trigger of WFD (White Feces Disease) outbreaks in aquaculture. This Vibrio spp. has an antibiotic resistance to Ampicillin, Co-Amoxiclav, Amoxicillin, Azithromycin, Actinobacteria and Ciprofloxacin HCL. Actinobacteria and alginate have been reported to increase the marine biota resistance against diseases through prebiotic and probiotic mechanisms. This study aims to discover and increase the secondary metabolite production of Actinobacteria-Alginate and its ability as anti-vibrio. Alginate extraction in the samples dated September 2020 originally from Teluk Awur Bays, Jepara, Central Java, Indonesia (33.73±1.84%) was considerably higher than in May 2021 (22.67±0.3%). Samples were taken from sediment and mangrove root. Actinobacteria strains are macroscopically and microscopically similar to the genus Streptomyces. The most well-known antibiotics were produced by Streptomyces spp. The anti-vibrio test was carried out by Kirby-Bauer disc diffusion. The results were observed by measuring the inhibition zone surrounding the paper disc using a digital calliper. Co-culture strain 90 together with alginate have an approved antibacterial activity against all Vibrio spp. in the concentration of 10.disc-1 mg and 5 mg.disc-1. Co-culture Actinobacteria with alginate has remarkably changed the green-yellow color to olive green/dark red-orange (strains 3, 62, 63, 72, and 90), indicating the transformation of the formation alginate with pigments into other compounds through the biosynthetic pathway. Therefore, alginate enables to support of Actinobacteria by induction the active secondary metabolite as an anti-vibrio to counteract the bacterial pathogen diseases.